Metode Pembelajaran Dasa Dharma Sebagai Implementasi Pendidikan Holistik - Pratiwi, Ni Kadek Sinta (Metta : Jurnal Ilmu Multidisiplin, 2022)
Education directs a person to make a better life. Through education can change a person into a character who has noble character, has sympathy and empathy for all creatures. The recent reality is that education only directs the achievement of intellectual intelligence but forgets emotional, spiritual and skill intelligence. It is necessary to re-develop holistic education by implementing learning models or methods in the educational process. The objectives to be achieved in the preparation of this research are to know about holistic education and the implementation of the Dasa Dharma learning method in holistic education. The method used is descriptive qualitative research. The results of this study can provide an overview of holistic education. Holistic education is education as a whole which includes intellectual, emotional, physical, social, aesthetic and spiritual potential. Various kinds of learning methods that can be used in holistic education. One of them is the dasa dharma method as the implementation of holistic education. The dasa dharma method includes dharma carita, dharma lila, dharma gita, dharma kriya, dharma shanti, dharma wacana, dharma yatra, dharma tula, dharma sadhana, and dharma brata.